Microsatellite loci and the complete mitochondrial DNA sequence characterised through next-generation sequencing and de novo genome assembly, and a preliminary assessment of population genetic structure for the Australian crane, Antigone rubicunda. (May 2019) - Miller, Adam D; Veltheim, Inka; Nevard, Timothy; Gan, Han Ming; Haase, Martin
The Brolga ( Antigone rubicunda ) is a large Australian crane species with a broad distribution spanning from the tropical north to the south-eastern regions of the continent. Brolga populations throughout New South Wales, Victoria and South Australia have been in decline since the early twentieth century, with the species being listed as vulnerable in each state. To aid future conservation of the species, its taxonomic status needs to be validated, and patterns of gene flow and population connectivity across the species distribution need to be understood. To assist future genetic studies, we developed a suite of polymorphic microsatellite markers and the complete mitochondrial genome sequence by next-generation sequencing. A total of 18 polymorphic loci were characterised using DNA extractions from 47 individuals, comprising 30 and 17 individuals from Victoria and northern Australia, respectively. We observed moderate genetic variation across loci with only a single locus deviating significantly from Hardy–Weinberg equilibrium. De novo and reference-based genome assemblies were used to assemble the A. rubicunda mitochondrial genome sequence, which consists of 16, 700 base pairs, and a typical metazoan mitochondrial gene content and arrangement. We test these new markers by conducting a preliminary analysis of genetic structure between south-eastern and northern Australian Brolga populations. Mitochondrial analyses provided evidence of shared haplotypes across the species range supporting the conspecific status of extant populations, while microsatellite markers indicated weak but significant genetic differentiation suggesting gene flow is limited. We discuss the implications of these findings and the benefits that these genetic markers will provide for future population genetic research on this iconic Australian bird species.